THE IMPLEMENTATION OF RISK-BASED INTERNAL AUDIT AS A MODERATING VARIABLE IN THE EFFECT OF INDEPENDENCE, COMPETENCE, AND AUDITOR ETHICS ON AUDIT QUALITY - Dian Dwi Hapsoro; Choirul Anwar; Ayatulloh Michael Musyaffi (Adisam Publisher, 2026)
This study aims to examine the effect of auditor independence, competence, and ethics on audit quality, with the implementation of Risk-Based Internal Audit (RBIA) serving as a moderating variable. The study was conducted on Government Internal Supervisory Apparatus (APIP) employed at inspectorates within ministries or government institutions in the political and law enforcement sectors. The study employed primary data collected through questionnaires. Data analysis was performed using SmartPLS version 4, with a sample of 112 auditors. The results indicate that independence, competence, and auditor ethics each have a positive and significant effect on audit quality. Furthermore, the implementation of Risk-Based Internal Audit as a moderating variable was found to strengthen the influence of auditor ethics on audit quality. However, it tended to weaken the influence of independence and competence on audit quality.